(untitled) (Journal of Hama University, 2019)
This study includes an analytical study of the effect of altering the parameters of the Messy Genetic Algorithm on its results in selecting the optimal solution for the design of a drinking water network and then comparing the obtained optimal solution with a number of scientific research results from the literature for a number of scientists. It has been found that the Messy Genetic Algorithm is better than the simple Genetic Algorithm, in terms of the ability to reach a less expensive solution and meet the hydraulic requirements, after comparing with a number of reference studies that were carried out in a similar way.